Climate Smart Village Project: Agroforestry - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) South Asia, is implementing climate smart agriculture practices, institutions, activities and policies in various Indian villages. The project is gathered under the umbrella name Climate Smart Villages. This video showcase how agroforestry can help farmers adapt and mitigate climate change. www.ccafs.cgiar.org